2009
DOI: 10.1055/s-0029-1210310
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lesions in the Limbic-Hypothalamic System on Metabolic Response of Acetate to Daily Repeated Immobilization Stress

Abstract: The effects of lesions in the basal medial hypothalamus and limbic structure on the acetate metabolic responses to daily repeated exposure to immobilization stress in the liver of rabbits have been investigated. The experimental results were as follows: (1) The acetate metabolic response to the 1st exposure to immobilization stress (exposure on the 1st day) were considerably altered by lesions in the periventricular arcuate nucleus (ARC) ventromedial hypothalamus (VMH), stria terminalis (ST) and dorsal fornix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Thus, the metabolic responses of pyruvate to the ist exposure to 1MO were altered by the ARC lesions, suggesting that the ARC participated in the mechanisms of pyruvate metabolic responses to the ist exposure to 1MO. Our previous findings suggested that the ARC also participated in the mechanisms of adrenocortical and acetate metabolic responses to the ist exposure to 1MO (Seto et al, 1982;Seto et al, 1984). In rabbits with ARC lesions, as in shamoperated animals, the 7th exposure to 1MO had no appreciable effects on the rates of 1C transfer into 002, G, KB, CE, TG, FC, FFA and PL.…”
Section: Methodsmentioning
confidence: 91%
See 4 more Smart Citations
“…Thus, the metabolic responses of pyruvate to the ist exposure to 1MO were altered by the ARC lesions, suggesting that the ARC participated in the mechanisms of pyruvate metabolic responses to the ist exposure to 1MO. Our previous findings suggested that the ARC also participated in the mechanisms of adrenocortical and acetate metabolic responses to the ist exposure to 1MO (Seto et al, 1982;Seto et al, 1984). In rabbits with ARC lesions, as in shamoperated animals, the 7th exposure to 1MO had no appreciable effects on the rates of 1C transfer into 002, G, KB, CE, TG, FC, FFA and PL.…”
Section: Methodsmentioning
confidence: 91%
“…From these findings and our present results, it might be suggested that the ARC was not concerned with the process of establishment of pyruvate metabolic adaptation to daily repeated exposures to 1MO. Our previous findings suggested that the ARC did not participate in the process of adrenocortical and acetate metabolic adaptation to daily repeated 1MO (Seto et al, 1982;Seto et al, 1984). Table 2 shows the effects of VMH lesions on the pyruvate metabolic responses to daily 1MO.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations